Konstruksi Identitas Nasionalisme dalam Pikukuh dan Buyut Masyarakat Adat Baduy - Armawi, Armaidy; Susilawati, Desy (Paradigma: Jurnal Kajian Budaya, 2021)
This research is entitled “Construction of Nationalism Identity in Baduy Society Based on Pikukuh and Buyut.” This is a library research on the philosophical life of the Baduy, a traditional community in Indonesia. Analysis was conducted using interpretation, inductive and deductive, internal coherence, and holistica approaches. This research resulted is some conclusions. First, the Baduy community was found to uphold a form of ethno- nationalism which is based on Pikukuh and Buyut with a strong focus on the meaning of leadership, communal life, and observance of laws. However, this ethno-nationalism does not conflict with the state nationalism upheld by the Indonesian government. Indeed, seba shows that there has always been good relationship between the Baduy people (which uphold ethno-nationalism) and the Indonesian government (which upholds state nationalism). Secondly, the “imagined” nationalism in the Baduy community is founded based on traditional bond, in which case nationalism is not separated from tradition. Consequently, the values are oriented towards basic rationality in order to construct an identity of nationalism unique to the Baduy community. However, at the same time, instrumental rationality and the value-oriented rationality have the same role, in that they serve to construct the meaning of nationalism in the Baduy community. All of these factors result in a harmonious relationship between ethno-nationalism upheld by the the Baduy community and state nationalism upheld by the Indonesian government.